Crazy Spiral: Doubles, Photographs and Portraits in L'anima degli altri by Alba de Céspedes (ENTHYMEMA, 2024)
Alba de Céspedes' L'anima degli altri (1935) is a literary work that serves as a laboratory for themes and stylistic elements that reappear in her later works. Despite being relatively unexplored by critics, it’s a fundamental experience in the author's body of work. The incorporation of images from a literary tradition linked to the preceding century allows us to observe its unique functioning throughout the stories. The contribution aims to investigate the functions of the double and its use in the stories through literary, pictorial, and photographic doublings. This study examines the connection between this theme and other typical elements of nineteenth-century fantastic literature, such as the magnetism of objects, the non-inertia of the inert, and madness. It observes how the identity of each character multiplies before destroying itself, and in each story, it is replaced by its own artistic replica, which becomes truer than the truth.
Keywords: Alba de Céspedes; Duality; Photography and Literature; Identity; Women's Writing